Individual Learning Plan (ILP) Effectiveness: EFL Islamic Students’ Writing Skill Enhancement - Rapi Hamdi Nur; Rendra Kusuma Wijaya (JELITA, 2024)
This study investigates the efficacy of implementing Individual Learning Plan (ILP) to enhance the writing skills of eleventh-grade students at MAS, (Madrasah Aliyah Swasta) Guppi Mamuju, an Islamic private senior high school in West Sulawesi, Indonesia. Conducted through a pre-experimental approach, the research population comprised eleventh-grade students from MAS Guppi Mamuju, totaling one class. Utilizing total sampling, one experimental class of eight students was selected. The study employed a writing test as the primary research instrument, assessing various aspects including content, organization, vocabulary, language use, and mechanics using Jacobs' scoring scale. Data analysis was conducted using Microsoft Excel's Automatic Data Analysis tool. The results indicated a notable improvement in students' writing ability following the implementation of ILP, as evidenced by the significant increase in mean scores from the pre-test (57.00) to the post-test (70.63), with a range of 13.37 points. Statistical analysis using the t-test supported the rejection of the Null Hypothesis (H0) and acceptance of the Alternative Hypothesis (H1). In conclusion, the integration of ILP effectively enhanced the writing skills of eleventh-grade students at MAS Guppi Mamuju.